Application of Photoacoustic Imaging for Lymphedema Treatment - Suzuki, Yushi; Kajita, Hiroki; Watanabe, Shiho; Okabe, Keisuke; Sakuma, Hisashi; Imanishi, Nobuaki; Aiso, Sadakazu; Kishi, Kazuo (Journal of Reconstructive Microsurgery, 2021)
Background Lymphatic vessels are difficult to identify using existing modalities as because of their small diameter and the transparency of the lymph fluid flowing through them.Methods Here, we introduce photoacoustic lymphangiography (PAL), a new modality widely used for lymphedema treatment, to observe limb lymphatic vessels. The photoacoustic imaging system used in this study can simultaneously visualize lymphatic vessels and veins with a high resolution (0.2 mm) and can also observe their three-dimensional relationship with each other.Results High-resolution images of the lymphatic vessels, detailed structure of the dermal back flow, and the three-dimensional positional relationship between the lymphatic vessels and veins were observed by PAL.Conclusion The clear image provided by PAL could have a major application in pre- and postoperative use during lymphaticovenular anastomosis for lymphedema treatment.
Keywords: lymphedema; lymphaticovenular anastomosis; lymphatic vessels; photoacoustic lymphangiography